Electrode|electrolyte interface enhancement in quasi-solid-state zinc-air batteries through an anion conducting polymer electrolyte interlayer by in situ polymerization - Kurian, Maria; Vijayakumar, Vidyanand; Manna, Narugopal; Kanheerampockil, Fayis; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2023)
This work introduces a novel concept of electrode|electrolyte interface enhancement using an ultraviolet (UV) light-assisted in situ polymerization strategy to improve the performance of quasi-solid-state zinc-air batteries (ZABs). The suitability of the UV polymerization strategy to process a mechanically stable OH- conducting anion exchange polymer electrolyte membrane (AEPEM) reinforced by a glass fiber (GF) separator is also reported. The in situ polymerized ionomer-skin/interlayer (a thin anion-conducting polymer coating over the air-cathode of ZAB) acts as a buffer layer to narrow down the performance gap generally observed between ZABs possessing quasi-solid-state electrolytes and standard liquid electrolytes, respectively. For instance, when combined with the in situ polymerization strategy, a rechargeable ZAB (rZAB) based on an AEPEM-GF composite membrane delivered a high power density of 140 mW cm(-2), higher than that of the one without an in situ polymerized ionomer interlayer (120 mW cm(-2)). Notably, in a flexible rZAB configuration, this new strategy resulted in enhanced rate capability and cycling stability for 14 h at an operating current density of 2 mA cm(-2).